Detection of SARS-CoV-2 on hospital surfaces - Pasquarella, Cesira; Colucci, Maria Eugenia; Bizzarro, Assunta; Veronesi, Licia; Affanni, Paola; Meschi, Tiziana; Brianti, Ettore; Vitali, Pietro; Albertini, Roberto (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 pandemic, affecting 213 countries, with more than 10 million cases and over 500,000 deaths is still causing serious health, social and economic emergency worldwide. Italian Northern regions are among the most badly affected areas. Surfaces represent matrices to which particular attention should be paid for prevention and control of SARS-CoV-2 transmission. A few studies have highlighted virus presence on surfaces. We report the evidence of its presence on hospital surfaces, in a single room hosting a patient whose nose-pharyngeal swab resulted positive for SARS-CoV-2 RNA at the admission. The surfaces sampling was carried out using pre-wetted swabs followed by extraction and amplification of viral RNA by reverse Real-Time Polymerase Chain Reaction (rRT-PCR). A total of 4/15 (26.66%) surfaces were positive for SARS-CoV-2 RNA: the right bed rail, the call button, the bed trapeze bar, the stethoscope; moreover, the patient’s inner surgical mask was positive, showing the emission of the virus from the patient. This study is a further confirmation that the surfaces represent a potential vehicle of transmission. This supports the need for strict adherence to hand and environmental hygiene.